무인전투기 물리적 전투력 분석 - 민승식(Seungsik Min); 오경원(Kyungwon Oh) (항공우주시스템공학회지, 2017)
The objective of this study was to use the Lanchester equation to predict the outcome of our engagement between our unmanned aerial vehicle (UAV) (Blue Group) and enemy UAV (Red Group). Lanchester's law states that the power of corps is proportional to the number of combatants. A second law states that the power of corps is proportional to the square of the number of combatants. The first law is a suitable law for guerrilla warfare while the second law is known as the law suitable for all-out war. Therefore, the second law is commonly used. The second law of Lanchester's was used in this study to predict engagement results. We estimated the battle loss rate value to win the battle as well as the required power number. We also predicted power number to make the damage of our group less than one. The battle loss rate to reliably receive victory when the enemy's UAV and the ally's UAV are equal in number of combat units must be 1: 1.5 or more. 본 논문은 란체스터 방정식을 이용하여 우리의 무인전투기(블루군)과 적 무인전투기(레드군) 간의 교전 결과를 예측하였다. 란체스터 법칙은 군단의 전력이 전투원 수에 비례한다는 제1법칙(linear law)과 전투원 수의 제곱에 비례한다는 제2법칙(square law)가 있다. 제1법칙은 게릴라전에 적합한 법칙이고 제2법칙은 전면전에 적합한 법칙으로 알려져 있으며 일반적으로 제2법칙이 많이 쓰인다. 란체스터의 제2법칙을 이용하여 교전 결과를 예측하였다. 교전에서 승리하기 위한 전투손실률 값은 물론 필요 전력수를 추산하였고, 우리 군의 피해를 1대 미만으로 만들기 위한 전력수도 예측하였다. 적 무인전투기와 아군 무인전투기의 전투 대수가 같을 경우 승리를 보장받으려면 전투손실률이 1:1.5 이상이 되어야 한다.